Enhanced Visible-Light Activity of Titania via Confinement inside Carbon Nanotubes - Chen, Wei; Fan, Zhongli; Zhang, Bei; Ma, Guijun; Takanabe, Kazuhiro; Zhang, Xixiang; Lai, Zhiping (Journal of the American Chemical Society, 2011)
Titania confined inside carbon nanotubes (CNTs) was synthesized using a restrained hydrolysis method. Raman spectra and magnetic measurements using a SQUID magnetometer suggested the formation of remarkable oxygen vacancies over the encapsulated TiO2 in comparison with nanoparticles dispersed on the outer surface of CNTs, extending the photoresponse of TiO2 from the UV to the visible-light region. The CNT-confined TiO2 exhibited improved visible-light activity in the degradation of methylene blue (MB) relative to the outside titania and commercial P25, which is attributed to the modification of the electronic structure of TiO2 induced by the unique confinement inside CNTs. These results provide further insight into the effect of confinement within CNTs, and the composites are expected to be promising for applications in visible-light photocatalysis.